2016
DOI: 10.1038/cdd.2015.162
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63 regulates IL-33 and IL-31 signaling in atopic dermatitis

Abstract: Atopic dermatitis (AD) is the most common inflammatory skin disease with no well-delineated cause or effective cure. Here we show that the p53 family member p63, specifically the ΔNp63, isoform has a key role in driving keratinocyte activation in AD. We find that overexpression of ΔNp63 in transgenic mouse epidermis results in a severe skin phenotype that shares many of the key clinical, histological and molecular features associated with human AD. This includes pruritus, epidermal hyperplasia, aberrant kerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 67 publications
(91 reference statements)
3
38
0
Order By: Relevance
“…In the digestive tract, IL‐33 is expressed by epithelial cells from salivary glands, mucosal surface of the stomach and gastric glands (Figure C), both in humans and mice . In the skin, IL‐33 expression is constitutive in murine keratinocytes but inducible in human keratinocytes, particularly during atopic dermatitis where it may be regulated by p53 family member p63 (specifically ΔNp63) . In our studies, we consistently observed nuclear IL‐33 staining in human skin keratinocytes and epithelial cells of the stomach, but we noticed significant variability between different cells, different part of the tissues and different individuals, suggesting local regulation by environmental cues .…”
Section: Cellular Sources Of Il‐33supporting
confidence: 51%
“…In the digestive tract, IL‐33 is expressed by epithelial cells from salivary glands, mucosal surface of the stomach and gastric glands (Figure C), both in humans and mice . In the skin, IL‐33 expression is constitutive in murine keratinocytes but inducible in human keratinocytes, particularly during atopic dermatitis where it may be regulated by p53 family member p63 (specifically ΔNp63) . In our studies, we consistently observed nuclear IL‐33 staining in human skin keratinocytes and epithelial cells of the stomach, but we noticed significant variability between different cells, different part of the tissues and different individuals, suggesting local regulation by environmental cues .…”
Section: Cellular Sources Of Il‐33supporting
confidence: 51%
“…TP63 also has an important role in the pathogenesis of atopic dermatitis, a chronic inflammatory skin disease (Rizzo et al . ). AP is also a chronic inflammatory disease of the periradicular tissues that is caused by microorganisms infecting the pulp tissues, therefore it can be hypothesized that TP63 likely plays a role in AP development.…”
Section: Discussionmentioning
confidence: 97%
“…Increased expression of TP63 was observed in epithelial cells and damaged parenchyma cells of lung after viral infections with H1N1 influenza virus (Kumar et al 2011, Zheng et al 2014, and in the olfactory epithelium during acute inflammatory response (Chen et al 2017). TP63 also has an important role in the pathogenesis of atopic dermatitis, a chronic inflammatory skin disease (Rizzo et al 2016). AP is also a chronic inflammatory disease of the periradicular tissues that is caused by microorganisms infecting the pulp tissues, therefore it can be hypothesized that TP63 likely plays a role in AP development.…”
Section: Discussionmentioning
confidence: 99%
“…Skin-specific expression of IL-4, IL-13, TSLP, and IL-33 elicited pruritic AD-like dermatitis (16, 3740). More recently, a study showed that transgenic expression of ΔNp63 resulted in keratinocyte activation and an AD-like phenotype (41). Several studies, including our own, have showed that chronic epicutaneous antigen exposure caused AD-like dermatitis and enhanced airway inflammation and airway obstruction after allergen inhalation challenge (21, 42).…”
Section: Discussionmentioning
confidence: 99%